ONTOGENETIC DEVELOPMENT OF SENSORY STRUCTURES ON THE ANTENNULES AND ANTENNAE OF THE GIANT RIVER PRAWN MACROBRACHIUM ROSENBERGII (DE MAN) - Cavalari Henriques, Virginia Maria; De Medeiros, Guilherme Fulgencio; New, Michael B.; Okada Nakaghi, Laura Satiko [UNESP]; Valenti, Wagner C. [UNESP] (Natl Shellfisheries Assoc, 2014)
In this study the occurrence of sensory structures on the antennules and antennae of the giant river prawn Macrobrachium rosenbergii (De Man) during postembryonic ontogenetic development were examined. Larvae and postlarvae were obtained from hatchery recirculating tanks, juveniles from indoor nursery tanks, and adults from earthen grow-out ponds. The animals were fixed with Karnovsky fixative and dissected. Antennules and antennae were removed, metal-coated, and photodocumented using a scanning electron microscope. The antennules have aesthetascs and simple plumose and pappose setae; the antennae have simple, plumose and pappose setae. These structures increase in density, covered surface, and distribution during ontogeny and should be related to chemoreception and mechanoreception. The antennular statocyst that appears during larval stage VII of the giant river prawn has an array of sensory structures that enable the perception of chemical and tactile stimuli beginning with its early life stages. The ontogenetic changes observed allow an inference that initial-stage larvae, advance-stage larvae, juveniles, and adults have different capacities to exploit the environment.
Keywords: aesthetascs; sensory structures; chemoreception; mechanoreception; antennule; antenna; Macrobrachium rosenbergii; giant river prawn